Changes in Knowledge After Education with Demonstration and Actions for Email Carries Treatment with Autraumatic Restrorative Treatment - Nike Haryani Tania Madinah; Damhuji Damhuji; Budi Suryana (Jurnal Kesehatan Gigi, 2022)
ABSTRACT Education is a learning process from not knowing to knowing. The provision of education is a very important need for human life so that the goals of the learning process or health education lead to the achievement of goals. Education, namely for behavior change, can be done by several methods, including lectures, discussions, demonstrations, simulations and others. There is also the provision of dental caries treatment with the Autraumatic Restorative Treatment technique as a form of early rescue effort that is carried out to prevent tooth decay from getting worse. This study aims to determine changes in knowledge and attitudes after being given education with demonstrations and actions for treating enamel caries with the Autraumatic Restorative Treatment technique. This research uses the type of research in the form of a cross sectional study. The population in this study consisted of grade 4.5 and 6 elementary school students. Sampling in this research using purposive sampling technique, namely sampling based on the researcher's assessment of who is eligible to meet the requirements as a sample. The results of this study indicate that there are changes in students' knowledge and attitudes after conducting education and before conducting education and there are differences in students' knowledge and attitudes before and after counseling. This study can be concluded that educational counseling about knowledge and attitudes of dental caries treatment can affect students' knowledge of gogo treatment in Autraumatic Restorative Treatment.Keyword : Knowledge,Attitude,Education,Autraumatic Restrorative Treatment